Oddział Wydzielony Wisła - zapomniana flotylla. Zarys działań (Kronika Bydgoska, 2018)
In the Second Republic of Poland, the Vistula River played an important role in the network of freight and passenger transport. However, considering the approaching war, it was becoming a barrier and a huge problem for efficient movement of the Polish army on both banks of the river. Lack of bridges and deficient antiaircraft defense caused concern for the Polish command. In order to solve this problem, the Vistula Detachment was delegated to Pomerania from the Pinsk Flotilla that operated in the faraway region of Polesie. The article describes the hopes placed in the detachment and their outcome as well as the fights taking place on the Vistula in 1939.